SDGs Learning Using Interactive Web-Based Satellite Imagery at SMAN 15 Semarang - Izzuddin Muhammad (Indonesian Journal Publisher, 2025)
The problem in teaching Sustainable Development Goals (SDGs) at the high school level is the lack of utilization of technology and the lack of contextual and interactive learning resources. This study aims to develop and implement interactive web-based satellite imagery as a learning media to improve students' understanding of SDG issues, particularly those related to the environment. The interactive web application was developed using the Google Earth Engine platform and Landsat 8, Sentinel-1, Sentinel-2, and Sentinel-5 data. The research method used was a pre-experimental design with a pretest-posttest group. The research subjects were 10th-grade social studies students at SMAN 15 Semarang studying geography lessons on maps, remote sensing, and geographic information systems. Data were collected through observation and tests. A science-based learning approach guided classroom teaching and learning. The results showed that integrating satellite image-based learning media into an interactive web platform increased students' understanding of the SDGs and remote sensing technology by 11%. These results indicate that using remote sensing technology and an interactive web provides an innovative and contextual learning alternative in SDG-based geography education in schools.